Dissecting the opposing regulatory functions of endogenous nitric oxide production in colorectal cancer initiation, adaptive immune response alterations, and ferroptosis execution - Tatode, Amol; Chaudhary, Anis Ahmad; Qutub, Mohammad; Trivedi, Rashmi; Umekar, Milind; Ali, Mohamed A. M.; Premchandani, Tanvi (Oncology Reviews, 2025)
Colorectal cancer (CRC) progresses through defined stages, from localized carcinoma in situ (Stage 0) to metastatic disease (Stage IV), with treatment strategies evolving from surgery in early stages to systemic therapies in advanced stages. Advances in biomarkers and genomic profiling have enabled personalized approaches, enhancing precision medicine. Nitric oxide (NO) plays a multifaceted role in CRC, acting as both a promoter and an inhibitor of cancer progression depending on its concentration, timing, and cellular context. At low concentrations, NO promotes angiogenesis, enabling tumor growth and metastasis. Conversely, high concentrations can exert anti-tumor effects, including the induction of cell death. Notably, its role in ferroptosis is biphasic: while high, exogenously delivered concentrations of NO can induce this iron-dependent cell death, lower, endogenously regulated levels can be protective by terminating lipid peroxidation. NO influences CRC by modulating the tumor microenvironment, mechanostress responses during metastasis, and signaling through extracellular vesicles (EVs), thereby aiding immune evasion. It also reprograms CRC cell metabolism, enhancing glucose utilization and mitochondrial activity to support growth in hypoxic conditions. The three nitric oxide synthases (NOS)—inducible NOS (iNOS), endothelial NOS (eNOS), and neuronal NOS (nNOS)—interact with hydrogen sulfide (H2S) to regulate oxidative stress and tumor growth. Targeting NO-related processes, such as ferroptosis, metabolic adaptations, and immune modulation, offers promising therapeutic advances to improve CRC treatment outcomes. This review highlights the dual role of NO in CRC, with particular focus on its novel mechanisms in ferroptosis, metabolism, immune modulation, and tumor–microenvironment interactions.